Characterization of AuNPs+rGO as a functionalized layer for LSPR sensors - Fantoni, Alessandro (2021)
Funding Information: Research supported by EU funds through the FEDER European Regional Development Fund and by Portuguese national funds by FCT Fundção para a Ciência e a Tecnologia with projects PTDC/NAN-OPT/31311/2017, UID/EEA/00066/2019, and by projects IPL/2019/BioPlas_ISEL and IPL/2018/aSiPhoto_ISEL.